Preparation of Hollow Titanium Dioxide Shell Thin Films from Aqueous Solution of Ti-Lactate Complex for Dye-Sensitized Solar Cells - Chigane, Masaya; Watanabe, Mitsuru; Shinagawa, Tsutomu (IntechOpen, 2011)
None